2013
DOI: 10.1097/sa.0b013e3182a492dd
|View full text |Cite
|
Sign up to set email alerts
|

Increased Long-term Mortality After a High Perioperative Inspiratory Oxygen Fraction During Abdominal Surgery

Abstract: A lthough a high perioperative inspiratory oxygen fraction (80%) has been recommended to avoid perioperative wound infections, one of the largest recent trials, the PROXI (perioperative oxygen inspired) trial, found no reduction in surgical site infection and a higher 30-day mortality rate in the group receiving 80% oxygen. In this follow-up study of the PROXI trial, the association between long-term mortality and perioperative oxygen fraction was assessed in patients undergoing abdominal surgery. From patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 3 publications
3
65
1
4
Order By: Relevance
“…The PROXI trial [125], that is a large, multicenter, randomized trial involving 1400 patients undergoing abdominal surgery, found no evidence of any beneficial effect of supplemental oxygen; in fact, SSI occurred in 131 of 685 patients (19%) receiving 80% oxygen and in 141 of 701 (20%) receiving 30% oxygen [odds ratio 0.94 (95% confidence interval 0.72-1.22), P = 0.64]. Indeed, a long-term follow-up study (median 2.3 years after surgery) found poorer survival in the supplemental oxygen group [126].…”
Section: Cmentioning
confidence: 99%
“…The PROXI trial [125], that is a large, multicenter, randomized trial involving 1400 patients undergoing abdominal surgery, found no evidence of any beneficial effect of supplemental oxygen; in fact, SSI occurred in 131 of 685 patients (19%) receiving 80% oxygen and in 141 of 701 (20%) receiving 30% oxygen [odds ratio 0.94 (95% confidence interval 0.72-1.22), P = 0.64]. Indeed, a long-term follow-up study (median 2.3 years after surgery) found poorer survival in the supplemental oxygen group [126].…”
Section: Cmentioning
confidence: 99%
“…1,2 Only recently, perioperative hyperoxia has been associated with higher patient mortality and morbidity although the detailed injurious mechanisms remain unknown. [3][4][5][6] While the effects of constant hyperoxia on the human body have been investigated to some extent, little is known with regard to cyclic hyperoxia that may occur during O 2 -administration in the presence of altered cardiac or pulmonary function. For example, cyclic hyperoxia can be caused by cyclic recruitment and derecruitment of lung atelectasis (cyclic atelectasis, CA) during high-dose O 2 -administration.…”
Section: Editorial Comment: What This Article Tells Usmentioning
confidence: 99%
“…39 However, recent studies have questioned a net beneficial effect of hyperoxia that seems associated with increased mortality and morbidity. [4][5][6] The mechanisms by which hyperoxia may harm the human body include increase in reactive O 2 -species, reduced organ blood flow, and disturbances in cellular redox balance. 1,2 The present study adds a novel concept to this topic by proposing that extreme constant and cyclic hyperoxia potentially may cause harm to the vascular endothelium by signaling pathways including the oxidative stress, NFjB, Notch, and PPAR pathway.…”
Section: Clinical Relevancementioning
confidence: 99%
“…High inspiratory oxygen concentrations have been associated with adverse outcomes in emergency medical conditions, including exacerbation of COPD, 28 resuscitation after cardiac arrest, [29][30][31] myocardial infarction, 32 and traumatic brain injury. 33 Additionally, treating perioperative patients with a high FiO 2 may be associated with increased mortality without reducing surgical site infections in surgical patients 34,35 and it might be linked to increased longterm risk of myocardial infarction. 36 These adverse outcomes may be caused by decreased local blood flow on normal and nondiseased vasculature induced by the vasoconstrictive effect of hyperoxaemia, 37 which have been described in the heart 38 and brain.…”
Section: How Oxygen Therapy Might Be Harmfulmentioning
confidence: 99%
“…32 Recently two meta-analyses of observational studies found an association between hyperoxaemia and mortality in critically ill patients. 50,51 Some single studies have indicated an association between hyperoxaemia and mortality, 23,29,35 whereas others have not. 18,[52][53][54][55] Finally, a new single centre randomised clinical trial conducted in a general ICU population, showed that a hyperoxaemic target level of PaO 2 resulted in markedly increased mortality as opposed to a more conservative approach with a PaO 2 target within the normal physiological range.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%